Facilitation of oral sensitivity by electrical stimulation of the faucial pillars - Tobias Braun (Nature Portfolio, 2021)
Abstract Dysphagia is common in neurological disease. However, our understanding of swallowing and its central nervous control is limited. Sensory information plays a vital role in the initiation of the swallowing reflex and is often reduced in stroke patients. We hypothesized that the sensitivity threshold of the anterior faucial pillar could be facilitated by either electrical stimulation (ES) or taste and smell information. The sensitivity threshold was measured by ES in the anterior faucial pillar region. The measurement was repeated 5 min after baseline. Thirty minutes after baseline, the participants underwent a test for taste and smell. Immediately after the test, the ES was repeated. Thirty healthy volunteers with a mean age of 27 ± 5.1 participated in the trial. Mean sensitivity threshold at baseline was 1.9 ± 0.59 mA. The values 5 min after baseline (1.74 ± 0.56 mA, p = 0.027) and 30 min after baseline (1.67 ± 0.58 mA, p = 0.011) were significantly lower compared to the baseline, but there was no difference between the latter (p = 0.321). After 5 min, a potentially facilitating effect was found on oral sensitivity by ES of the faucial pillar area. Thirty minutes later, this effect was still present. Trial registration Clinicaltrials.gov, NCT03240965. Registered 7th August 2017— https://clinicaltrials.gov/ct2/show/NCT03240965 .